2012
DOI: 10.1111/j.1532-7078.2012.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant Attention to Dynamic Audiovisual Stimuli: Look Duration From 3 to 9 Months of Age

Abstract: The goal of this study was to examine developmental change in visual attention to dynamic visual and audiovisual stimuli in 3‐, 6‐, and 9‐month‐old infants. Infant look duration was measured during exposure to dynamic geometric patterns and Sesame Street video clips under three different stimulus modality conditions: unimodal visual, synchronous audiovisual, and asynchronous audiovisual. Infants looked longer toward Sesame Street stimuli than geometric patterns, and infants also looked longer during multimodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…However, the developmental changes found in our study differ in some respects from those found in these prior studies. For example, Reynolds et al (2013) found a decrease in attention to a complex social event (Sesame Street), both silent visual and audiovisual, across 3- to 9-months of age, and Courage et al (2006) found an increase in looking to silent social events from 6.5- to 12-months. These inconsistencies are likely due to differences in stimuli (social events depicting Sesame Street vs. speaking faces), methods, and measures (habituation time vs. length of longest look, or average look length).…”
Section: Discussionmentioning
confidence: 99%
“…However, the developmental changes found in our study differ in some respects from those found in these prior studies. For example, Reynolds et al (2013) found a decrease in attention to a complex social event (Sesame Street), both silent visual and audiovisual, across 3- to 9-months of age, and Courage et al (2006) found an increase in looking to silent social events from 6.5- to 12-months. These inconsistencies are likely due to differences in stimuli (social events depicting Sesame Street vs. speaking faces), methods, and measures (habituation time vs. length of longest look, or average look length).…”
Section: Discussionmentioning
confidence: 99%
“…In habituation or familiarization paradigms, a repeated stimulus is presented until visual attention wanes to a predefined level; the looking duration during this learning phase is proposed as a stable measure of individual differences in infancy (Colombo, 1997; Reynolds, Zhang, & Guy, 2012) and is considered to reflect information processing efficiency and sustained attention to a stimulus (e.g., Reynolds & Guy, 2012; Shaddy & Colombo, 2004). In low risk and typically developing infants, attention to faces during habituation is often longer than to objects with significant decreases in time to habituation over the first year of life (Jones, Pascalis, Eacott, & Herbert, 2011; Jones et al, 2015; Reynolds et al, 2012; Robledo, Kolling, & Deák, 2010).…”
Section: Early Developmentmentioning
confidence: 99%
“…In low risk and typically developing infants, attention to faces during habituation is often longer than to objects with significant decreases in time to habituation over the first year of life (Jones, Pascalis, Eacott, & Herbert, 2011; Jones et al, 2015; Reynolds et al, 2012; Robledo, Kolling, & Deák, 2010). In contrast, 6-month-old high risk infants who later met criteria for ASD (compared to high risk infants without early ASD) showed a significantly shorter peak look that was later in the habituation function, suggestive of disruptions to sensitization and deeper levels of processing (see Jones et al, 2015).…”
Section: Early Developmentmentioning
confidence: 99%
“…Although prior research has investigated differences in looking to audiovisual versus visual stimulation, particularly in infants (Bahrick, Todd, Castellanos, & Sorondo, 2016; Reynolds, Zhang, & Guy, 2013), this research has focused primarily on measures of look duration. Little research has characterized differences in speed, scanning patterns, or strategies for exploring audiovisual and visual stimulation.…”
Section: Discussionmentioning
confidence: 99%